Jean la Perle (Yuḥannā al-Ğawharī). Un martyr copte bien connu - Fayez, Nabil Farouk (2007)
Contrary to what the author of a recent contribution claimed, the martyr John the Pearl (Yūḥannā al Ǧawharī) is well attested in Copto-Arab hagiographic sources.